Estimation of Evapotranspiration ill a Rice Irrigation Scheme in Peninsular Malaysia - Lee, Teang Shui; Mohamed Najim, Mohamed Mujithaba; Haque, Md. Aminul; Huang, Yuk Feng (Universiti Putra Malaysia Press, 2005)
The correct estimation of ET in the water balance equation allows for improved water management in rice cultivation. Eight evapotranspiration estimation methods (Penman, Penman-Monteith, Pan Evaporation, Kimberly-Penman, Priestley-Taylor, Hargreaves, Samani-Hargreaves and Blaney-Criddle) were tested with 30 years of daily data, at a study site in the west coast of Peninsular Malaysia. The estimation of evapotranspiration by all methods showed the same trend throughout the year. The Samani-Hargreaves method gave the highest estimation followed by the Priestley-Taylor and Hargreaves methods. The Penman-Monteith method gave the lowest estimations of evapotranspiration followed by the Blaney-Criddle method and then the Pan method. The Penman-Monteith, Blaney-Criddle and Pan methods gave lower values of evapotranspiration with no significant difference among them (P = 0.05). All the other estimation methods were significantly different from these three methods. The Penman method, though was different from the three methods in terms of development; however, it estimates evapotranspiration close to these three methods. The Penman-Monteith, Blaney-Criddle and Pan were found to be the better methods to estimate evapotranspiration in the study area. Results from this study showed that the Penman method can be used to get somewhat reasonable estimates though it tends to overestimate evapotranspiration. Comparisons of these selected methods against the PenmanMonteith method showed that they have good correlation. The Pan, BlaneyCriddle and Penman gave correlation coefficients of 0.87, 0.55 and 0.97 respectively. A simple correlation equation, developed using 3D-year daily data, showed that direct measurement of net radiation can be used to estimate reference evapotranspiration with considerable accuracy (r2 = 0.97)